Action Tracer with Android API - Chiramba, Humphrey (Department of Electrical Engineering, 2024)
This dissertation aims to present the design and testing of a low-cost motion capture device with feedback capabilities. In addition to this, an API to communicate with this system is developed that allows devices to connect to the motion capture system and execute commands on it. This system, Action Tracer, would be useful in cases where a user may need to train or learn a repetitive motion found in an activity or sport. Such a task needs to be done under supervision and may need to be done away from a coach or therapist. In either situation, a system which can accommodate both cases while providing insights that are not visible to the eye is needed. In addition to this, the system would need to be con gurable for the various sports that it may be used with, as well as be operated from an Android device. Most of the work that will be presented in this report will relate to the development of marker based motion capture systems, with a particular interest in the use of Inertial Measurement Units (IMUs). In addition to this, the subject of Biofeedback is be covered, as well as how it relates to motion capture and how it can be applied in this eld.